Apocalipsa dupa soferi - Solomon, Alexandru (Romania : Hi Film Productions, 2008)
A film about the personality shaping power of city traffic. The director chose five protagonists whom he accompanied on their everyday route around the Romanian capital, Bucharest: a countryside delivery boy , a half-paralyzed man who drives around helping others; a Peruvian-born mother of three, driving her sons to school each day; a father who has recently lost his daughter in a traffic accident; and a rock-fan traffic policeman. The way people drive and the way the traffic looks becomes a metaphor for the way society functions.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films